Imago Dei: Sebuah Upaya Membaca Alkitab Sebagai Perempuan Indonesia Dalam Konteks Perdagangan Orang di Nusa Tenggara Timur - Ira D. Mangililo (Indonesian Journal of Theology, 2017)
This paper examines the close connection between the domain of biblical interpretation and the communal sphere, which is comprised of living data that serves as starting point for scriptural interpretation. The yield of such interpretations serves as an important contribution for a church seeking proactively to address and resolve various urgent concerns in the current context. This essay considers one such crisis needing to be addressed: the issue of human trafficking in East Nusa Tenggara, with specific regard to how female victims of human trafficking have been torn apart by the variegated forms of oppression they have undergone. By looking to Genesis 1:26-27, with its emphasis on the concept of imago Dei, this paper demonstrates just how useful is a postcolonial approach to reading scripture, namely in the case of female victims who are reconsidering the manner in which they regard and understand themselves; no less than are men, women too are created in the image of God and, therefore, have in the sight of God an equality and parity of status with men. Equality and parity become a strong foundation upon which to resist every effort to debase the dignity and value of women. Furthermore, this article highlights the role of the community, namely as an agential collective set to oppose any attempt to rob fellow human beings of their claim, namely as living persons created according to God’s image.